Assess the Efficacy of Health Information on Knowledge Regarding Post Dialysis Home Care among Caretakers of Haemodialysis Patients - et al., Yogesh A. Jadhav (International Journal of Advanced Science and Technology, 2020)
Objectives were to assess the level of knowledge regarding post dialysis home care among caretakersof patients undergoing hemodialysis, to evaluate the effectiveness of health information on postdialysis home care among caretakers of patient undergoing hemodialysis and to determine knowledgewith the selected demographic variables among caretakers of patient undergoing hemodialysis.Method: one group pretest posttest design was used to conduct the study among caretakers ofhemodialysis patients and totally 50 caretakers were selected by Purposive Sampling technique.Ethical permission was obtained before the data collection. After obtaining permission from thesetting, the caretakers were asked their willingness to participate in the study and informed consentwas obtained. The demographic variables were collected by using structure interview questionnaire.During pre-test the Caretakers knowledge of post dialysis home care was measured by multiplechoice questions, which had 30 questions for 15 minutes. Then the subject received Healthinformation Programme regarding post dialysis home care for 30 minutes. On 7th day post-test wasdone by researcher as like pre-test to assess the effectiveness of Health information Programme onKnowledge regarding post dialysis home care among Caretakers of Chronic Renal Failure patientsundergoing hemodialysis. Results: There was a significant difference between pre-test and post-testscores on knowledge regarding Post Dialysis Home Care among Caretakers. Calculated value of ‘t’was greater than tabulated value t at 5% level of significance. Conclusions: The educationalprogramme regarding post dialysis home care is a vital role in improving caretaker’s knowledge ofpost dialysis home care.